ANALYSIS OF IR SPECTRA OF SKIN OF CATTLE, SHEEP AND GOATS (Scientific journal of the Fergana State University, 2024)
Skins of cattle, sheep and goats. Washed and dried. The dried skins were ground into powder and the IR spectra were studied. Bending vibrations (NH2) and stretching vibrations of the carbon group (CO) were also observed in the IR spectrum. The literature was compared and analyzed.